A Quantum Circuit for the Brazilian Decimetric Array (BDA) Signal Correlation - Violin, Renato de O.; Saito, Jose Hiroki; Sawant, Hanumant Shankar (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2010: Anais do XI Simpósio em Sistemas Computacionais de Alto Desempenho, 2010)
Quantum computing is a novel way to perform computation based on quantum physics. Since its beginning, at 1985, it promises a revolution in the data processing. Works that have been done prove that quantum computing, regarding its features provided by quantum physics, offer high data processing power compared with classical computation. The aim of the present work is to develop a quantum circuit to perform the signal correlation of Brazilian Decimetric Array (BDA), a radio interferometer that has been developed by National Institute of Space Research (INPE). It was studied some possible circuits and they were compared with classical ones, with respect to the number of logical operations needed to perform the correlation, over a 100 ms integration period. The results show that the proposed quantum circuit uses less logical operations than the classical circuit. Although we don't have yet technology to build quantum computers, with the same efficiency of the semiconductors, it may be feasible in the future, so that the proposed implementation makes sense.